Communicating climate change: conduits, content, and consensus - Pearce, Warren; Brown, Brian; Nerlich, Brigitte; Koteyko, Nelya (Wiley, 2015)
Climate change has been the subject of increasing efforts by scientists to understand its causes and implications; it has been of growing interest to policymakers, international bodies, and a variety of nongovernment organizations; and it has attracted varied amounts of attention from traditional and, increasingly, online media. These developments have been aligned with shifts in the nature of climate change communication, with changes in how researchers study it and how a variety of actors try to influence it. This article situates the theory and practice of climate change communication within developments that have taken place since we first reviewed the field in 2009. These include the rise of new social media conduits for communication, research, and practice aimed at fine tuning communication content, and the rise to prominence of scientific consensus as part of that content. We focus in particular on continuing tensions between a focus on the part of communicators to inform the public and more dialogic strategies of public engagement. We also consider the tension between efforts to promote consensus and certainty in climate science and approaches that attempt to engage with uncertainty more fully. We explore the lessons to be learnt from climate communication since 2009, highlighting how the field remains haunted by the deficit model of science communication. Finally, we point to more fruitful future directions for climate change communication, including more participatory models that acknowledge, rather than ignore, residual uncertainties in climate science in order to stimulate debate and deliberation.